Facing Authority A Theory of Political Legitimacy - Fossen, Thomas (Oxford University Press, 2024)
When your friends call on you to take to the streets and demand the fall of the regime, this presses a practical predicament that we all address, often implicitly, in our everyday lives: Is this regime legitimate? Facing Authority investigates the ways in which this question of legitimacy can be addressed in theory and practice, in the face of disagreement and uncertainty. Instead of asking, "What makes authorities legitimate?" in the abstract, it examines how the question of legitimacy manifests itself in practice. How can we distinguish whether a regime is legitimate, or merely purports to be so? And what does it mean to do this well? Facing Authority proposes that judging legitimacy is not a matter of applying moral knowledge, provided by political philosophy, but of engaging in various forms of political contestation-contestation over the representation of power (what is the nature of the regime?), collective selfhood (who am I, and who are we?), and the meaning of events (what happened here-a coup, or a revolution?). These questions constitute the heart of the question of legitimacy, but thus far they have been neglected by theorists of legitimacy. This book offers a new way of thinking about political legitimacy and practical judgment, interweaving philosophical analyses of key concepts (including representation, identity, and temporality) with concrete examples of struggles for legitimacy, from the German Autumn to the Arab Spring. The result is a pragmatist alternative to predominant moralist and realist approaches to legitimacy in political philosophy.